Analisis Strategi Pengembangan Bahan Tanam Klon Karet Unggul Pada Agribisnis Karet Rakyat di Propinsi Sumatera Utara - Asrul Asrul; Azwana Azwana (Universitas Medan Area, 2018)
Rubber (Hevea brasiliensis Muel Arg.) is a commodity that make country devisa .the goverment have decided the development of national rubber policy from increasing clon using to more than 85% with minimal productivity rate 1500 kg/ha.Purpose of the research is to know the strength/weakness and chance/threat also to analisys the development of rubber clon material for citizen rubber agribuisness in North Sumatera province. North Sumatera province have strength in development of rubber clon material for citizen rubber agribuisness such as have plantation resource, goverment support, rubber farmer resource, and have weakness in seeds resource root stock. Entres resource and the currency control by the charge agency. The cost of the natural rubber is much better now, high request for excellent rubber seeds, in globalisation trading era have chance in development rubber clon material for citizen rubber agribuisness in notrh sumatera province and have threat such as the competition with palm oil commodity, rubber seeds marketing system that not yet efficient also the investation that not fully condusif. The priority strategic in development of excellent rubber clon material for citizen rubber agribuisness in north sumatera province is : 1) rubber entres plantation seeds resource investation and purification entres plantation 2) investation and determine seeds resource plantation for root stock, 3) to build the plantation of rubber entres seeds resource in central location of the contruction for citizen rubber plantation 4) increasing quality seeds control by the charge agency. Key words : excellent clon, rubber entres, rubber agribuisness